Blockchain Coupled Oracle Fusion - Satpathy, Diptikant (Indian Journal of Computer Science, 2018)
With stricter compliance and policy requirements, demanding customers, commercial competition, geographically spread businesses, and vulnerable cyber security, today’s multifaceted business sees a lot more challenges than ever before. To overcome these challenges, there is a need to track and trace each aspect of the business process. Maintaining an extra protected automated system with transparency, security, reliability, and traceability has a big impact on the bottom line of business organizations. A technology called Blockchain provides a viable solution to the problems associated with the complex business process traceability. The blockchain architecture and design is based on distributed ledger technology (DLT). The Blockchain technology was first theorized to be used for a cryptocurrency called ’Bitcoin’ for a peer-to-peer online payment in 2008 (in a white paper published by Satoshi Nakamoto). Off late, it has begun to witness success in finding applications in many other fields like banking, asset management, healthcare, travel, supply chain, logistics, identity management, etc. Here we discuss industrial applications of Blockchain in an Oracle Enterprise Resource Planning (ERP) Cloud environment. As per a study by Forbes, about 90% of the Fortune 500 companies work on some or the other Enterprise Resource Planning (ERP) platform (single or multi-ERP systems). By 2020, four out of every ten large organizations will have atleast 60% of their businesses on Cloud. Hence, Blockcha,in in a business scenario needs to have an integration with already existing ERP systems and furthermore with future cloud systems. Oracle Blockchain Cloud service offers easy application integration with plug-and-play adapters providing PaaS delivery.